Photoreaction and photopolymerization studies on phenoxazin dyes/diphenyliodonium chloride salt - Gomez, María Lorena (2007)
The photophysics and photochemistry of the dyes resazurin (Rz) and resorufin (Rf) in absence and presence of diphenyliodonium chloride (DPIC) were investigated in water at pH 10. The dye/DPIC combination undergoes photoreaction via intermolecular electron transfer, resulting in photobleaching of the dye and generation of active radical species released by subsequent decomposition of DPIC. The polymerization of acrylamide in aqueous solution on visible irradiation in the presence of resazurin without the onium salt was negligible. However, it proceeds efficiently in the presence of DPIC. The polymerization follows a typical radical chain mechanism with second order termination. In the case of Rf/DPIC the photobleaching is very important, and no appreciable polymerization occurs. © 2006 Elsevier B.V. All rights reserved.